pengaruh metode PBL dan FGD terhadap hasil belajar PAI kelas X RPL di SMKN 1 Dlanggu - Mukhlisatun Listyawati; Muhammad Nizar Al-Ajis (Amaliyatu Tadris (AMYTA), 2026)
This study aims to determine the effect of Problem Based Learning (PBL) and Focus Group Discussion (FGD) methods on student learning outcomes in Islamic Religious Education (PAI) class X RPL at SMKN 1 Dlanggu. This study used a quantitative quasi-experimental method with two groups, namely the experimental class using the PBL model with FGD and the control class using the conventional learning model. The research instrument was an essay test consisting of 5 questions given in the pretest and posttest. The results showed that the initial abilities of both classes were equal, with an average pretest score of 46.79 for the PBL class and 47.31 for the conventional class. After being given treatment, the posttest results showed an average score of 81.14 for the conventional class, higher than the PBL class with FGD which obtained an average score of 76.98. Nevertheless, both methods proved effective in improving student learning outcomes significantly, with an increase of 30.19 points in the PBL class and 33.83 points in the conventional class. This research provides implications that the selection of learning methods must be adapted to student characteristics, learning materials, and implementation context, not only based on the novelty or popularity of the method.